2000
DOI: 10.1074/jbc.275.17.12917
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Studies of the Effects of Anti-factor H Antibodies on Complement-mediated Lysis

Abstract: We have recently reported that complement factor H, a negative regulator of complement-mediated cytotoxicity, is produced and secreted by most bladder cancers. This observation was exploited in the development of the BTA stat™ and BTA TRAK™ diagnostic assays, both of which make use of two factor H-specific monoclonal antibodies in sandwich format. Here we show that both antibodies exert interesting effects on the biochemistry of complement activation in in vitro systems. Antibody X13.2 competes with C3b for as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2002
2002
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 33 publications
1
4
0
1
Order By: Relevance
“…This indicates that the presence of C3b in urine samples should not have an effect on binding of the mAb to FH in the diagnostic procedure. In concordance with these results, it has previously been reported that mAb X52.1 actually enhances the strength of association of FH with C3b (28 ). In contrast, our finding that the presence of FHR-1 reduced the binding of FH to X52.1 in the BTA TRAK assay indicates that the presence of FHR-1 in a patient's urine sample can affect the BTA TRAK test result.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This indicates that the presence of C3b in urine samples should not have an effect on binding of the mAb to FH in the diagnostic procedure. In concordance with these results, it has previously been reported that mAb X52.1 actually enhances the strength of association of FH with C3b (28 ). In contrast, our finding that the presence of FHR-1 reduced the binding of FH to X52.1 in the BTA TRAK assay indicates that the presence of FHR-1 in a patient's urine sample can affect the BTA TRAK test result.…”
Section: Discussionsupporting
confidence: 91%
“…It has previously been shown that mAb X52.1 does not inhibit cofactor activity of FH for C3b cleavage in the fluid phase (28 ). To test whether C3b or its fragment C3d could compete with X52.1 in binding to FH, we used a sensitive surface plasmon resonance analysis.…”
Section: Analysis Of the Effects Of Mab X521 On The Interaction Betwmentioning
confidence: 99%
“…The BTA‐Stat test is a point‐of‐care test approved by the Food and Drug Administration (FDA) for use as an aid in the management of bladder carcinoma patients in conjunction with cystoscopy (BTA‐Stat product insert). The BTA‐Stat is an immunoassay that qualitatively detects the presence of a human complement factor H‐related (hCFH‐r) protein in the urine of bladder carcinoma patients 57, 58. The hCFH‐r protein is very similar to human complement factor‐H (hCFH) and is produced by bladder carcinoma cells 59.…”
mentioning
confidence: 99%
“…son inmunoensayos enzimáticos destinados a la medición de la proteína relacionada con el factor H del complemento humano (hCFHrp) en orina utilizando los dos anticuerpos monoclonales X13.2 y X52.1 21,22 . Las células tumorales de la vejiga son hCFHrp que se liberan en la orina, presumiblemente para protegerse de ser destruidas por el sistema del complemento 23 En varios estudios 24-31 la sensibilidad global del ensayo BTA TRAK fue del 64% (intervalo 56-72%) y la especificidad global del 71% (51-95%) (Tabla 2).…”
Section: Prueba Immunocyt / Ucyt+unclassified